فقه السياسة الشرعية عند الإمام ابن عبد البر المالكي من خلال كتابيو التمهيد والاستذ كار - مسائل الإمامة العظمى أنموذجا- - سلمان, علي (University of Eloued جامعة الوادي, 2020)
"يدكر موضوع ىذه الدراسة حوؿ: مسائل الإمامة العظمى، كأت٪وذج في فقو السياسة الشرعية عند الإماـ ابن عبد البر ات١الكي، من خلبؿ كتابيو التمهيد كالاستذكار، كقد جاءت لتوضيح الاستفهاـ الذم يقوؿ: ت١اذا الاعتناء بالتًاث العلمي لابن عبد البر ات١الكي حديثيا كفقهيا كتارتٮيا .. كفي ات١قابل قلة العناية بو سياسيا في أحكاـ الإمامة العظمى؟ رغم ات١وسوعية، خاصة في التمهيد كالاستذكار!. كقد ق ّسمت ىذه الدراسة على مبحثتُ تٖتهما مطالب، فات١بحث الأكؿ: للتعريف بالإماـ ابن عبد البر ات١الكي، كالتعريف بكتابيو التمهيد كالاستذكار، كات١بحث الثاني: خصص لفقو الإمامة العظمى عند الإماـ ابن عبد البر، كذلك بتعريفها ك ذكر حكمها كمقاصدىا كركائزىا، كحقيقة الإماـ الأعظم، كمفهوـ الرعية، كصلة الإمامة بالعلبقات ات٠ارجية، كأت٫ية الولاية على الرعية.كتوصلت ىذه الدراسة للكشف عن القيمة العلمية لاستنباطات كتعليقات الإماـ ابن عبد البر في مسائل الإمامة العظمى، ككفرتها في كتا ْبي التمهيد كالاستذكار، كأنو ت٬در بالباحثتُ في الإمامة العظمى العناية باستثمار ما سطره الإماـ اب"This Subject of studying talks about the affair of the Great Imama « Leading « as a sample of Fikh « Understanding » of Legitimate politics of the Maliky Ibn Abd Albarr, through is both books “Tamhid” “Introduction” and “Istithkar” “ Doing or Asking for remembering” It emergrd to make this interregation clear wich says: why there is care of the scientific legacy of the Maliky Ibn Abdelbarr through Hadith “speech” Fikh “Understanding” and Historically… And on contrary there is a lack of care of it politically in the rules of the Great Imama? Inspite of the encyclopedia especially in Tamhid and Istithkar I divided this study into tow themes, including each there are issues; the first theme: for defining of Imam Ibn Abdelbarr, and defining of his both books Tamhid and Istithkar; whereas the second theme is devoted for “Fikh” of the Great Imama of through defining it and including its rules, its goals, its supports, the reality of the Great Imam, the meaning of the citizens, the relation of the Imama with the foreign relation, and the importance of the “Walaya” reign on citizens. This study reatched at uncovering of the scientific value of the deductions and comments of Great Imama, its abundance in both books Tamhid and Istithkar, and its worthy for the researcher in the Great Imama to care for exploiting of what Imam Imam Ibn Abdelbarr has written in it"
مذكرة ماستر تخصص فقه مقارن واصوله
Keywords: فقه السياسة - الشرعية - الإمام ابن عبد البر المالكي - التمهيد - الاستذكار; Jurisprudence of politics - legitimacy - Imam Ibn Abd al-Barr al-Maliki - introduction - recall